Endometrial carcinoma in young women: management options and its review - Lekhi, Anshika; Manchanda, Rahul; Jain, Nidhi; Chithra, Sravani; Kausar, Hena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Endometrial carcinoma is a disease of older postmenopausal women, and is relatively uncommon in patients younger than 40 years. The incidence in young women is 2%-14%. Endometrial carcinomas in this age group may be familial, associated with Lynch syndrome, or sporadic. Patients usually have increased exposure to estrogen. Its treatment includes hysterectomy, bilateral salpingoophorectomy and pelvic lymphadenectomy and in some cases, radiation therapy. Preservation of fertility is a major challenge encountered in such cases. Before deciding on the management of any patient with abnormal bleeding a hysteroscopic examination with biopsy should be performed for all the patients, as hysteroscopy make it easy to visualize the cavity and to obtain the biopsy from the specific site. We have reviewed the literature of endometrial cancer management in young women through a case in a 35-year-old woman with previous 3 cesarean treated for abnormal uterine bleeding. We performed Hysteroscopy which showed adenocarcinoma endometrium on histopathology. Most endometrial carcinomas presenting in this young age are associated with estrogen excess. Pathologically they are usually low-grade endometrioid carcinomas with lower stage and are associated with favourable clinical outcomes. With this review the authors emphasize the need of hysteroscopic endometrial reckoning in young females with abnormal bleeding before starting any medical treatment. Also highlighting the management options in such cases where fertility preservation holds a significant challenge.